Surgical Management of Tentorial Notch Meningioma Guided by Further Classification: A Consecutive Study of 53 Clinical Cases - Qin, Chaoying; Wang, Junquan; Long, Wenyong; Xiao, Kai; Wu, Changwu; Yuan, Jian; Pan, Yimin; Zhang, Chi; Su, Jun; Yuan, Xianrui; Liu, Qing (Frontiers in Oncology, 2021)
Background: Management of tentorial notch meningiomas (TNM) remains a challenge for neurosurgeons. We demonstrate the clinical characteristics and surgical experiences of TNM based on our cases according to a proposed further classification. Methods: We retrospectively analyzed clinical and follow-up data in a consecutive series of 53 TNM patients who underwent microsurgical operation from 2011 to 2019 in our institution. The operations were performed using various approaches. Clinical history, preoperative and postoperative neurofunction, imaging results, and surgical outcomes were collected for further classification of TNM. Results: All TNM cases were divided into anterior (T1), middle (T2), and posterior notch (T3). According to the direction of tumor extension and correlation with the neurovascular structures, detailed subtypes of anterior TNMs were identified as the central (T1a), posterior (T1b), and medial type (T1c). The middle TNMs were divided into the infratentorial (T2a), supratentorial (T2b), and supra-infratentorial type (T2c). The posterior TNMs were divided into superior (T3a), inferior (T3b), lateral (T3c), and straight sinus type (T3d) in reference to Bassiouni’s classification. Total removal of the tumor was achieved in 46 cases, with 5 cases of subtotal and 2 cases of partial removal without any recorded deaths in our series. In total, 5 subtotal resected cases underwent gamma-knife treatment and achieved stable disease. Postoperative aggravation or new onset cranial nerve dysfunction occurred in some individual cases, with incidences ranging from 3.77% to 15.10% and improved preoperative neurological deficits ranging from 0% to 100%. Conclusion: Further, TNM classification based on the intracranial location, extension direction, relationship with brainstem and neurovascular structures guides preoperative evaluation, rational surgical approach selection, and surgical strategy formulation. Taking microsurgery as the main body, a satisfactory outcome of TNM treatment can be achieved for complicated tumors by combining stereotactic radiotherapy. This study demonstrates the surgical outcomes and complications in detail. Further classification might be helpful for treatment decisions in the future.